The Effect Of Information Asymmetry And Internal Control On Accounting Fraud With Integrity As A Moderating Variable - Sri Nuraini Rahmawati; Yeshana Chirinna (Yayasan Az Zukhruf Cendikia, 2025)
Purpose - This study aims to examine the effect of information asymmetry and internal control on accounting for accounting, with integrity as a moderating variable, in the Indonesian logistics sector. Design/Methodology/Approach - This research uses quantitative approach with data collected through questionnaires from 150 employees of PT Indocitra Logistics Express (Access Logistics) distributed via social media. Each questionnaire contained 51 statements to be answered by respondents. The data analysis was executed using the Partial Least Square Structural Equation Modeling (PLS-SEM) methode, version 3.0. Findings - The results showed that information asymmetry has a positive and significant influence on accounting conditions. In contrast, internal control has a positive but insignificant effect. Furthermore, integrity is shown to strengthen the relationship between information asymmetry and financial accounting, but does not strengthen the relationship between internal control and financial accounting. Research Limitations/Implications - This study is limited to logistics and shipping sub-sector companies, so the results cannot be generalized to other sectors. Future research is recommended to explore additional factors that may affect accounting conditions, such as organizational culture and information technology. Originality/Value - This research provides new insights into the importance of integrity in mitigating the negative impact of information asymmetry on accounting, particularly in the Indonesian logistics sector. The findings are relevant for practitioners and policy makers to develop accounting condition mitigation strategies.